2022
DOI: 10.18240/ijo.2022.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of orbital apex syndrome in COVID associated mucormycosis patients in a tertiary care hospital

Abstract: AIM: To share clinical pattern of presentation, the modalities of surgical intervention and the one month post-surgical outcome of rhino-orbito-mucormycosis (ROCM) cases. METHODS: All COVID associated mucormycosis (CAM) patients underwent comprehensive multidisciplinary examination by ophthalmologist, otorhinolaryngologist and physician. Patients with clinical and radiological evidence of orbital apex involvement were included in the study. Appropriate medical and surgical intervention were done to each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Orbital apex syndrome is a rare presentation of mucormycosis that include ophthalmoplegia and rapid vision loss, involving cranial nerves II, III, IV, V, and VI and requiring anti-fungal and surgical debridement ( 21 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Orbital apex syndrome is a rare presentation of mucormycosis that include ophthalmoplegia and rapid vision loss, involving cranial nerves II, III, IV, V, and VI and requiring anti-fungal and surgical debridement ( 21 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies providing evidence on the impact of COVID-19 on the eye [1][2][3][4][5][6][7][8][9][10][11][12][25][26][27][28] , few of them focus on its impact on visual perception [13][14][15] . The present study has shown that there appears to be an impairment of color and achromatic-chromatic contrast vision in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Srivastava et al reported that the prevalence of orbital apex involvement is as high as 34.8% in COVID-19-associated mucormycosis (CAM). Among these patients, 74.2% had a vision of light perception that subsequently led to permanent loss of vision [ 2 ]. In diabetics, orbital apex syndrome secondary to mucormycosis may initially present as a partial ophthalmoplegia and is felt to represent microvascular disease, especially when there are minimal sinus findings by CT scan [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of steroids has been mandated as a life-saving response to COVID-19. There has been a significant increase in the number of mucormycosis cases post-COVID-19 worldwide because of the widespread use of steroids, especially in patients with preexisting poorly controlled diabetes mellitus [ 2 ].…”
Section: Introductionmentioning
confidence: 99%